2009
DOI: 10.1159/000216836
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Black Tea Polyphenols (Catechins and Theaflavins) against <i>Candida </i>Species

Abstract: Background/Aims: The polyphenols catechins and theaflavins in black tea have been shown to possess many medicinal properties, including anticancer activity and some antifungal characteristics, but there have been few studies of their anti-Candida activity. In this paper we report the results of our study of the anti-Candida activity of tea polyphenols. Methods: The effects of 4 different concentrations of catechins and theaflavins were evaluated on 5 isolates each of 5 Candida species employing an agar diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 40 publications
4
41
0
1
Order By: Relevance
“…(Martinez and Garcia-Casanovas., 2006). Black tea polyphenols (catechins and theaflavins) present activity on Candida species (Sitheeque et al, 2009), but when Almajano et al, (2008) comparatively analyzed infusion teas, the anticandidal activity was higher in non-fermented teas. However, their study was performed in a different strain of Candida, C. albicans ATCC 1002, under extractive conditions with a different methodology than the present study.…”
Section: The Antifungal Susceptibility Testingmentioning
confidence: 99%
“…(Martinez and Garcia-Casanovas., 2006). Black tea polyphenols (catechins and theaflavins) present activity on Candida species (Sitheeque et al, 2009), but when Almajano et al, (2008) comparatively analyzed infusion teas, the anticandidal activity was higher in non-fermented teas. However, their study was performed in a different strain of Candida, C. albicans ATCC 1002, under extractive conditions with a different methodology than the present study.…”
Section: The Antifungal Susceptibility Testingmentioning
confidence: 99%
“…The polyphenols, catechins and theaflavins isolated from Sri Lankan black tea, although the grades are not specified, are shown to have antifungal activities against 5 Candida species: C. albicans, Candida glabrata, Candida parapsilosis, Candida krusei, and Candida tropicalis [8]. We have previously shown that the three grades of tea used in this study contained substantial amounts of catechin and theaflavins [11,12].…”
Section: Discussionmentioning
confidence: 97%
“…and OP) belonging to the three agro-climatic elevations (low, mid and high) of the country [4]. The in vitro technique used to ascertain the antifungal activity was a widely employed inexpensive and well-established method [7,8]. Methanolic extracts were employed since they were the most common solvent used in investigation of plant products for anti-fungal activity [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated the antifungal activity of white and black teas, which is due to the differential preparation of the terminal leaves and apical buds of the plant Camellia sinensis (L.) (Almajano et al, 2008;Friedman, 2007;Sitheeque et al, 2009). One study demonstrated that the antifungal activity of these teas and their individual component, theaflavin digallate inhibited the growth of Trichophyton mentagrophytes and Trichophyton rubrum (Okubo et al, 1991).…”
Section: Introductionmentioning
confidence: 99%